2016
DOI: 10.1590/01047760201622042222
|View full text |Cite
|
Sign up to set email alerts
|

PULP PRODUCED WITH WOOD FROM Eucalyptus TREES DAMAGED BY WIND

Abstract: Wind may damage eucalyptus trees, especially 24 months after planting, which can reduce wood fiber quality and hinder pulp production. The objective of this study was to evaluate the use of these materials in mixtures with wood from seven-yearold trees to produce pulp. Bleached pulp was produced using 100, 95, 85, 75 and 0% wood from seven-year-old eucalyptus trees, related to cutting age. Wood from two-yearold trees, when trees are most susceptible to damage by wind, completed each treatment. A 5 cm thick dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…This also occurred with drainage, because the greater connection numbers hamper the water passing through the pulp (Gharehkhaniaet al, 2015). This behavior was reported for cellulose pulp from grasses (Andrade e Colodette, 2016), softwoods Chen et al, 2017) and hardwoods (Zanuncio et al, 2016).…”
Section: Alkaline Fi Ltrate Recirculation and Cellulosic Pulp Qualitysupporting
confidence: 70%
See 1 more Smart Citation
“…This also occurred with drainage, because the greater connection numbers hamper the water passing through the pulp (Gharehkhaniaet al, 2015). This behavior was reported for cellulose pulp from grasses (Andrade e Colodette, 2016), softwoods Chen et al, 2017) and hardwoods (Zanuncio et al, 2016).…”
Section: Alkaline Fi Ltrate Recirculation and Cellulosic Pulp Qualitysupporting
confidence: 70%
“…The softwood tear index was reduced, even at low levels of refinement, as reported for Pinus massonianae and China Fir . In hardwoods, the tear index increased at the initial refinement levels due to the increase of connections and decreased at more intense refinement levels due to fiber degradation (Gharehkhania et al, 2015), as reported for Corymbia citriodora (Severo et al, 2013) and Eucalyptus grandis × Eucalyptus urophylla (Zanuncio et al, 2016).…”
Section: Alkaline Fi Ltrate Recirculation and Cellulosic Pulp Qualitysupporting
confidence: 62%
“…T h e h i g h e r o r g a n i c a l o g e n s ( O X ) concentration of the pulp, increased by 36.7% compared to the control with the addition of the carryover, was due to the increased ClO 2 consumption during bleaching. These values were still acceptable for ECF pulp (< 200 gClt -1 ) as those below 30 gClt -1 of OX were suitable for ECF light processes (Sixta 2006).…”
Section: Pulp Chemical Properties After Bleachingmentioning
confidence: 90%
“…The increased in the compounds oxidised by permanganate and resulted in a kappa number of 2.2 and final brightness of 87.2% ISO. The higher H 2 SO 4 load in the acid hydrolysis stage A (Table 1) of the pulps in relation to the control sequence was due to the carryover alkalinity (Sixta 2006). The increased in pH negatively impacted the chlorine dioxide stage and increased its consumption (Sevastyanova et al 2012, Ferraz & Ventorim 2018.…”
Section: Alkaline Filtrate (Carryover) Recirculation and Chemical Reagent Consumptionmentioning
confidence: 99%
See 1 more Smart Citation